(untitled) (International Journal of Current Engineering and Technology, 2014)
Small satellite’s are now paving way for the students to explore and demonstrate cutting edge technologies, prove the same and implement it on bigger satellites. Thermal control plays a major role in satellite development due to the harsh temperature conditions it is subjected to in space. It has to be considered in order to have the smooth functioning of the satellite, this paper describes the thermal environment for a Twin Nano Satellite named STUDSAT-2.